2016
DOI: 10.29244/jmo.v4i2.12621
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Persepsi Konsumen dan Strategi Pemasaran Beras Analog (Analog rice)

Abstract: <p><em>Analog rice is artificial ricewhose material is not from paddy, but it is made from a variety of local flour (corn, sago and shorgum). As a new product, Rice Analog require appropriate marketing strategies through analysis of consumer perception. This research purposes are to develop a marketing strategy through identification Analog Rice segmentation, targeting and positioning based on consumer perception. The analytical method used were crosstabs analysis, cluster analysis and biplot analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
2
0
6
Order By: Relevance
“…Sumarwan et al, (2015) menjelaskan bahwa persepsi konsumen terhadap produk sangat memengaruhi keputusan pembelian hunian ramah lingkungan. Andrianto et al, (2013), serta Hubeis dan Titus (2016) menjelaskan bahwa semakin baik persepsi konsumen terhadap nilai pangan organik, semakin tinggi minat konsumen untuk membeli pangan organik tersebut. Dapat dikatakan bahwa Bukalapak belum merespon temuan terdahulu dengan baik.…”
Section: Pendahuluanunclassified
“…Sumarwan et al, (2015) menjelaskan bahwa persepsi konsumen terhadap produk sangat memengaruhi keputusan pembelian hunian ramah lingkungan. Andrianto et al, (2013), serta Hubeis dan Titus (2016) menjelaskan bahwa semakin baik persepsi konsumen terhadap nilai pangan organik, semakin tinggi minat konsumen untuk membeli pangan organik tersebut. Dapat dikatakan bahwa Bukalapak belum merespon temuan terdahulu dengan baik.…”
Section: Pendahuluanunclassified
“…To increase the sales and consumption of artificial rice in the community, there have been several studies conducted to develop an artificial rice marketing strategy. These studies revealed that the most appropriate marketing strategy is to focus on maintaining the product's quality and functionality that offers health benefits and high nutritional value, increasing the promotional activity, expanding the distribution area, and last but not least, focusing the market segments into adult (30-40 years old) that has an income level of IDR 4.000.000-6.000.000 [24,25].…”
Section: Artificial Rice Position In Current Marketmentioning
confidence: 99%
“…Kriteria yang dipilih untuk dijadikan responden penelitian meliputi (1) konsumen "beras analog" yang dipasarkan di gerai Serambi Botani dan (2) segmentasi pasar "beras analog" yang mengacu hasil penelitian Rizki et al (2013), yaitu dengan kriteria perempuan berusia ≥ 31 tahun, status menikah, tingkat pendidikan minimal S1, dan tingkat pendapatan perbulan ≥ Rp 4.500.000 Data dianalisis secara deskriptif, kuantitatif, dan distribusi frekuensi kategori (Sulistiyowati dan Astuti, 2016), sehingga mendapatkan informasi mengenai atribut yang menjadi pertimbangan dalam membeli beras. Output yang didapatkan digunakan sebagai input dalam pembuatan kuesioner pada tahap berikutnya.…”
Section: Tahapan Penelitianunclassified